Rheological study of CO2 hydrate slurry in the presence of Sodium Dodecyl Sulfate in a secondary refrigeration loop. (2nd February 2017) - Oignet, Jérémy; Delahaye, Anthony; Torré, Jean-Philippe; Dicharry, Christophe; Hoang, Hong Minh; Clain, Pascal; Osswald, Véronique; Youssef, Ziad; Fournaison, Laurence
Abstract: Secondary refrigeration and thermal energy storage are promising solutions to enhance the performance of refrigeration systems and reduce the impact of refrigerants on the environment. To improve the energy efficiency of secondary refrigeration loops, phase change material (PCM) slurries with a high energy density, such as CO2 hydrate slurries, can be used as a secondary refrigerant. In addition, hydrate-based processes could be an innovative option to capture CO2 from flue gas. In both applications, the rheological properties of the CO2 hydrate slurry have to be controlled. In the present study, CO2 hydrate slurry in the presence of Sodium Dodecyl Sulfate (SDS) was studied in a dynamic flow loop. The results show that SDS used at concentrations of 1500–2000 ppm significantly decreases agglomeration and improves the flow properties of the slurry. Moreover, SDS helps decrease the viscosity of the CO2 -hydrate slurry at high fraction (>10 vol%) and therefore could be suitable for use in industrial applications such as secondary refrigeration, in which hydrate slurries must be easy to handle. Highlights: Viscosity of CO2 hydrate slurry with SDS is measured with capillary viscometer method. Viscosity increases with hydrate fraction. Flow properties are improved above 10% of CO2 hydrate fraction with SDS. SDS has an anti-agglomerant effect on the CO2 hydrate slurry. The Herschel-Bulkley model was used to modelling the slurry viscosity.